Interference between ER stress-related bZIP-type and jasmonate-inducible bHLH-type transcription factors in the regulation of triterpene saponin biosynthesis in Medicago truncatula - Ribeiro, Bianca; Erffelinck, Marie-Laure; Lacchini, Elia; Ceulemans, Evi; Colinas, Maite; Williams, Clara; Van Hamme, Evelien; De Clercq, Rebecca; Perassolo, Maria; Goossens, Alain (Frontiers in Plant Science, 2022)
Triterpene saponins (TS) are a structurally diverse group of metabolites that are widely distributed in plants. They primarily serve as defense compounds and their production is often triggered by biotic stresses through signaling cascades that are modulated by phytohormones such as the jasmonates (JA). Two JA-modulated basic helix-loop-helix (bHLH) transcription factors (TFs), TRITERPENE SAPONIN BIOSYNTHESIS ACTIVATING REGULATOR 1 (TSAR1) and TSAR2, have previously been identified as direct activators of TS biosynthesis in the model legume Medicago truncatula. Here, we report on the involvement of the core endoplasmic reticulum (ER) stress-related basic leucine zipper (bZIP) TFs bZIP17 and bZIP60 in the regulation of TS biosynthesis. Expression and processing of M. truncatula bZIP17 and bZIP60 proteins were altered in roots with perturbed TS biosynthesis or treated with JA. Accordingly, such roots displayed an altered ER network structure. M. truncatula bZIP17 and bZIP60 proteins were shown to localize in the nucleus and appeared to be capable of interfering with the TSAR-mediated transactivation of TS biosynthesis genes. Furthermore, interference between ER stress-related bZIP and JA-modulated bHLH TFs in the regulation of JA-dependent terpene biosynthetic pathways may be widespread in the plant kingdom, as we demonstrate that it also occurs in the regulation of monoterpene indole alkaloid biosynthesis in the medicinal plant Catharanthus roseus.